Kinematic Alignment in Cruciate Retaining Implants Improves the Biomechanical Function in Total Knee Arthroplasty during Gait and Deep Knee Bend - Kang, Kyoung-Tak; Koh, Yong-Gon; Nam, Ji Hoon; Kwon, Sae Kwang; Park, Kwan Kyu (The Journal of Knee Surgery, 2020)
Kinematic alignment (KA), which co-aligns the rotational axes of the components with three kinematic axes of the knee by aligning the components to the prearthritic joint lines, has been a recently introduced surgical technique. However, whether KA and cruciate retaining (CR) implants provide better biomechanical function during activities than mechanical alignment (MA) in posterior stabilized (PS) implants is unclear. We evaluated the biomechanical functions during the stance phase gait and deep knee bend, with a computer simulation and measured forces in the medial and lateral collateral ligaments and medial and lateral contact stresses in the polyethylene insert and patellar button. The forces on the medial collateral ligament in KA were lower than those in MA in both CR and PS TKA in the stance phase gait and deep knee bend conditions, whereas those on the lateral collateral ligament did not show any difference between the two surgical alignment techniques in the stance phase gait condition. The maximum contact stresses on the medial PE inserts in KA were lower than those in MA in both CR and PS TKA in the stance phase gait and deep knee bend conditions. However, the maximum contact stresses on the lateral PE inserts and the patellar button did not differ between MA and KA. The biomechanical function was superior in KA TKA than in MA TKA, and KA was more effective in CR TKA. This comparison could be used as a reference by surgeons to reduce the failure rates by using KA TKA instead of MA TKA.
Keywords: total knee arthroplasty; kinematic alignment; mechanical alignment; finite element analysis